Reconstructing Teachers’ Language Intervention for Phonological Aspects in EFL Classroom - Susanto, Susanto; Nanda, Deri Sis; Ishak, Wan Irham (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Teachers’ language intervention can play a key role in helping students in the classroom interaction to learn a foreign language. In this paper, we discuss the teacher’s language intervention for phonological aspects in the English as a Foreign Language (EFL) classroom. We used a qualitative descriptive approach with a phenomenological research design. As the data, we recorded the language exchanges between the students and their teachers at the fifth year of a Primary School (Sekolah Dasar) in Bandar Lampung, Indonesia. We categorized three types of teachers’ language intervention, i.e. focalization, correction, and solicitation. Focalization intervention is manifested by the production of a lexical element. The intervention was observed in three situations, namely when reading familiar and unfamiliar English short stories, and playing a game with cards containing English words with their respective pictures, introduced in the stories. The teachers’ language interventions were coded in relation to phonological aspects, i.e. phoneme, syllable, and rhyme. The results show that there are 159 interventions in total. The teachers’ language interventions have the number of speech turns and the duration of the interactions varied in accordance with the context of situation, the Speech-turns mostly occur in reading unfamiliar English stories either for focalization, correction, or solicitation. Thus, this study concluded that teachers intervened more often in reading time of unfamiliar English stories, used focalization more frequently in the intervention, and utilized syllables more preferably as the focus in the intervention. As the implication, variability in the frequency and nature of interventions by the teachers could be at the origin of the differences observed in the performance of students.